Foaming and curing an aqueous epoxy foam using microwave - Erny Raudhoh Mohd Shafie (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
This study reports the effects of microwave energy, water content, and blowing agent concentration to the morphology, mechanical and thermal properties of aqueous epoxy foam based on polyamide-epoxy adduct. Samples of microwave energy were prepared at 160 to 320 watts of different microwave energy level and the samples of variation water content were formulated by using 25 to 200 phr of water content.